Prevalence and Risk Factors of Myopia among Medical students - Abdul Malik, Mohammad Hamza Bin; Mohydin, Mahnoor; Saeed, Aamir; Arif, Mariam; Abdul Malik, Mohammad Awais Bin; Mohydin, Shahmeer; Sami, Amtul Musawir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To access the prevalence and investigate the contributing risk factors of myopia in M.B.B.S students impacted by medical school lifestyle practices Methodology: A cross-sectional study was conducted for a period of two months between September and October of 2020, among the students of Services Institute of Medical Sciences, Lahore, Pakistan. Data was collected by using questionnaires from medical students. IRB approval was granted. Descriptive analysis was done using the research tool SPSS 25. Results: Out of 110 medical students, majority were male and 83.6% were myopic. Off which, 56.4% had a refractive error less than -3.00 D, 22.7% had a refractive error between -3.00 D to -6.00 D and 1.8% above -6.00 D. About 61.8% students had the onset of myopia in their adult age, while 23.6% since childhood. 54 students have a myopic familial history. Students spent most of their time doing near work like studying with 58.2% students reported use of digital devices (also at night). Most of the students wear prescription glasses, with 67.3% use it while writing. About 73.6% students do not take rest after doing work. About 70% students do not do any hourly outdoor exercise. Only 12.7 % of the students have an intake of vitamin A supplements. 97 % students do not have any history of ocular trauma, ocular surgery and laser treatment. Conclusion: Proper measures need to be taken by health authorities and medical college’s student affairs department to guide the students on how to improve heathy eye hygiene and routines. Regular ocular checkups should also be encouraged. It is recommended for students to study in good light, take proper rest, reduce their nutritional deficiencies and most importantly limit their screen time, especially at night. Health education programmers and medical education policy makers should be involved to ensure the implementation of frameworks that facilitate the control of risk factors of myopia amongst medical students.